2016
DOI: 10.1002/lno.10266
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of extracellular superoxide production by Trichodesmium colonies from the Sargasso Sea

Abstract: Reactive oxygen species (ROS) are key players in the health and biogeochemistry of the ocean and its inhabitants. The vital contribution of microorganisms to marine ROS levels, particularly superoxide, has only recently come to light, and thus the specific biological sources and pathways involved in ROS production are largely unknown. To better understand the biogenic controls on ROS levels in tropical oligotrophic systems, we determined rates of superoxide production under various conditions by natural popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 60 publications
(91 reference statements)
8
71
0
Order By: Relevance
“…For example, according to a recent study, corals may release external hydrogen peroxide to facilitate feeding on zooplankton or as a mode of defence against pathogens regulated by physical and chemical stimuli67. Consistent with the ability of superoxide to act as a cell density-dependent growth promoter, and with previous observations from phytoplankton and heterotrophic bacteria68, we found that extracellular superoxide production by actively developing coral larvae was inversely related to larval density (Supplementary Fig. 3).…”
Section: Discussionsupporting
confidence: 89%
“…For example, according to a recent study, corals may release external hydrogen peroxide to facilitate feeding on zooplankton or as a mode of defence against pathogens regulated by physical and chemical stimuli67. Consistent with the ability of superoxide to act as a cell density-dependent growth promoter, and with previous observations from phytoplankton and heterotrophic bacteria68, we found that extracellular superoxide production by actively developing coral larvae was inversely related to larval density (Supplementary Fig. 3).…”
Section: Discussionsupporting
confidence: 89%
“…Despite a widespread ability of marine microbes to produce extracellular superoxide, the reasons for this process and underlying mechanisms remain unclear. Extracellular superoxide production rates are dependent upon physiological and environmental factors, such as cell growth stage, cell density, light intensity, iron availability, and overall nutrient availability (Rose et al ; Diaz et al , ; Hansel et al ; Schneider et al ; Hansel et al ). The data we present in this study expand the number of organisms known to display cell‐density–dependent superoxide production to include additional eukaryotic algae, picocyanobacteria, and picobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that these photosynthetic organisms may produce significant internal ROS from light‐dependent processes, but we show here that these organisms are also prolific producers of superoxide in the dark. Furthermore, light has been shown to increase extracellular superoxide levels by some phytoplankton (Hansel et al ; Schneider et al ; Zhang et al ; Diaz et al ), suggesting that these organisms may be even greater sources of marine superoxide, depending on prevailing light conditions. The significant superoxide flux suggested by our measurements has further implications on trace nutrient cycling within the ocean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesser, ). In line with this, high superoxide production by field‐collected Trichodesmium colonies has been observed (Hansel et al ., ). Accumulation of O 2 and reactive oxygen species in the colony microenvironment may therefore increase the risk of oxidative stress in colonies compared with single trichomes and might be part of the reason why colonies showed lower N 2 and C fixation rates.…”
Section: Discussionmentioning
confidence: 97%